Influence of Seamless Patient-Centered Care on Efficiency, Satisfaction, and Patient Awareness in Imaging Departments: A Prospective Cohort Study - Yan, Shouzhen; Luo, Xiaohua; Xia, Qianzhi; Luo, Shijie; Xu, Feng (Current medical imaging reviews, 2024)
This study aimed to enhance the existing nursing model in imaging departments by implementing a characteristic seamless nursing care approach and assessing its impact on patient and medical staff satisfaction, nursing quality, examination efficiency, and patient awareness. We hypothesized that the implementation of a seamless nursing care model would be associated with higher patient satisfaction, improved nursing quality, increased examination efficiency, and better patient awareness compared to the traditional nursing model. This prospective cohort study included 300 patients undergoing imaging examinations from January 2019 to January 2022. Subjects were divided into control and observation groups (n=150 each) based on different nursing methods. The control group received routine care, and the observation group received seamless care. The following outcome measures were assessed using validated questionnaires: patient satisfaction (measured using a 5-point Likert scale), medical staff satisfaction with patient examination cooperation (measured using a 5-point Likert scale), nursing quality compliance rate (percentage of nursing tasks performed according to established guidelines), dissatisfaction rate (percentage expressing dissatisfaction with examination cooperation), and effect evaluation [measured using a knowledge test validated in previous studies (Chung et al., 2020) with a total score range of 0-20]. Average imaging examination and nursing times were significantly lower in the observation group compared to the control group (P<0.05). The examination cooperation dissatisfaction rate was significantly lower in the observation group (P<0.05). There were significant differences in examination precautions, procedures, breathing training methods, and injection comparisons between the groups (all P<0.05). The application of seamless nursing care may be associated with improved patient satisfaction, nursing service quality, imaging examination efficiency, and patient awareness of imaging examinations. However, further research is needed to establish causal relationships.